Multinational Corporation as a Regional Economic Security Network - Aliona DANILIUC (Eastern European Journal of Regional Studies)
This paper is about multinational enterprises and regional security economic, summarizes and synthesizes different strands of literature, to present conclusions on the potential role of multinational enterprises in regional economic security in the EU, Ukraine, Moldova. The circumstances under which 'developmental' MNE subsidiaries may emerge in host regions are reviewed and possible routes to cluster formation and the generation of dynamic comparative advantage are explored. Policy issues are discussed, emphasizing the importance of investment in infrastructure, education and other public goods.